2019
DOI: 10.1111/jcmm.14724
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of GAS5 ameliorates myocardial ischaemia/reperfusion injury via the miR‐335/ROCK1/AKT/GSK‐3β axis

Abstract: Growth arrest‐specific transcript 5 (GAS5), along non‐coding RNA (LncRNA), is highly expressed in hypoxia/reoxygenation (H/R)‐cardiomyocytes and promotes H/R‐induced apoptosis. In this study, we determined whether down‐regulation of GAS5 ameliorates myocardial ischaemia/reperfusion (I/R) injury and further explored its mechanism. GAS5 expression in cardiomyocytes and rats was knockdown by transfected or injected with GAS5‐specific small interfering RNA or adeno‐associated virus delivering small hairpin RNAs, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 34 publications
4
51
0
Order By: Relevance
“…For instance, GAS5 was upregulated in atherosclerosis, suggesting that GAS5 implicated in the development of atherosclerosis [22]. Moreover, the expression levels of GAS5 remarkably increased in epilepsy and ischemic heart disease [23,24]. Additionally, in this study, we found that GAS5 expression signi cantly downregulated in osteosarcoma, which was also consistent with some reports.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, GAS5 was upregulated in atherosclerosis, suggesting that GAS5 implicated in the development of atherosclerosis [22]. Moreover, the expression levels of GAS5 remarkably increased in epilepsy and ischemic heart disease [23,24]. Additionally, in this study, we found that GAS5 expression signi cantly downregulated in osteosarcoma, which was also consistent with some reports.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, miR-335 disturbed proliferation and migration, while promoting radiosensitivity of melanoma by inhibiting ROCK1. The miR-335/ROCK1 axis regulated multiple functions, including tumor progression (19)(20)(21), myocardial ischemia/reperfusion (22), and chondrogenesis (23). Lynch and colleagues firstly illustrated the negative feedback loop among miR-335/ROCK1-noncanonical TGF-β signaling and MYCN (24).…”
Section: Discussionmentioning
confidence: 99%
“…Primary neonatal rat cardiomyocytes were isolated from 1-day-old Wistar rats and cultured as described in our previous study. 17 Briefly, neonatal rats were sacrificed by decapitation and hearts were harvested. The ventricles were further separated and minced into 1 mm 3 pieces, followed by digestion with 0.05% pancreatin and 0.01% collagenase.…”
Section: Primary Neonatal Rat Cardiomyocyte Culturementioning
confidence: 99%